AYUSH for COVID-19: Science or Superstition? - Ritu Priya; V Sujatha (Wolters Kluwer Medknow Publications, 2020)
There is a lot of discussion on COVID-19 control strategies from the mainstream approaches, but it is also necessary to examine the contributions of the Ayurveda, Yoga and Naturopathy, Unani, Siddha, Sowa Riga and Homeopathy (AYUSH) sector, which is now being brought into public health interventions nationally. Although the AYUSH sector had previously joined the management of dengue and chikungunya outbreaks in some Indian states, its participation has remained contentious and there is reluctance in mainstream public health discourses to seriously examine their interventions. This is a commentary on the efforts made by the Ministry of AYUSH, state AYUSH directorates, AYUSH research institutions, and public hospitals, based on official documents as well as official statements reported in the media, with the aim of bringing out concerns in the process of adapting traditional textual knowledge and practices to public health requirements of the current age.